2007
DOI: 10.1097/01.tme.0000270339.19380.16
|View full text |Cite
|
Sign up to set email alerts
|

Educational Preparation of Nurse Practitioners and Physician Assistants

Abstract: This article provides an overview of the differences and similarities in educational preparation of nurse practitioners (NPs) and physician assistants (PAs) along with requirements for entry into each program, graduation, and certification. Using an exploratory descriptive design, a convenience sample of 50 NP and 50 PA programs was accessed over the Internet. The major finding in this study is that high-quality educational requirements exist for both NPs and PAs. NPs and PAs are educated under very different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…Although the professional practice of the NP and the PA has developed into one that tends to mirror the other, the differences in the education and background of its professionals are well documented. An exploratory descriptive study conducted in 2007 examined many important differences in the educational preparation of the NP and the PA (Bednar et al, 2007). The author utilized a convenience sample technique to examine and compare 50 NP and 50 PA programs.…”
Section: Educational Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the professional practice of the NP and the PA has developed into one that tends to mirror the other, the differences in the education and background of its professionals are well documented. An exploratory descriptive study conducted in 2007 examined many important differences in the educational preparation of the NP and the PA (Bednar et al, 2007). The author utilized a convenience sample technique to examine and compare 50 NP and 50 PA programs.…”
Section: Educational Preparationmentioning
confidence: 99%
“…The author utilized a convenience sample technique to examine and compare 50 NP and 50 PA programs. Bednar et al (2007) did identify that the study was limited by the relatively small sample size. The study revealed five major differences between NP and PA educational preparation.…”
Section: Educational Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in comparing the didactic content, both NP and PA programs are more similar than they are different, and each has a high quality of educational standards (Bednar et al, 2007). Nurse practitioner's practice focuses on a holistic approach to patient care, focusing on health education, patient advocacy, and health promotion versus the disease-focused approach of PA education (Urgent Matters E-Newsletter, 2010).…”
mentioning
confidence: 99%